Situation Report: Hungary, 12 November 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The New System of Economic Regulators (VII): Agriculture New Financial Incentive System for Managers Five-Year Cultural and Academic Co-operation Agreement with USSR Bottlenecks in the Educational System Sixth National Conference of Pioneer Leaders